2006
DOI: 10.1016/j.jvs.2005.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of risk factors associated with femoral pseudoaneurysms after cardiac catheterization

Abstract: Due to the development of technology and experience, more and more diagnostic and interventional catheterization procedures are performed on a daily basis. In our study, a high volume of cases in a particular room and use of large catheters were important risk factors for FPA complications. When these situations are combined with other risk factors (such as obesity, diabetes mellitus, hypertension, and arteriosclerosis), giving particular attention to local compression therapy would be more crucial to decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 14 publications
1
50
1
5
Order By: Relevance
“…The risk of vascular complications was established at 0.02-9% [7,8,12,14,17]. This wide range of results occurred due to varying criteria for diagnosing vascular complications, different diagnostic procedures (subjective symptoms, physical examination, duplex US) and inclusion of patients undergoing varied diagnostic and therapeutic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of vascular complications was established at 0.02-9% [7,8,12,14,17]. This wide range of results occurred due to varying criteria for diagnosing vascular complications, different diagnostic procedures (subjective symptoms, physical examination, duplex US) and inclusion of patients undergoing varied diagnostic and therapeutic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the reported incidence may vary from 0.2% to 7.7% according to the screening methods, either systematic Doppler US or guided by clinic signs [1,[4][5][6][7].…”
Section: Incidence and Diagnosismentioning
confidence: 99%
“…Many risk factors have been described at varying degrees in the literature: age of patients, female gender, larger sheath size(≥ 7F), arterial hypertension, body mass index, low femoral puncture and interventional procedure [1,4,8,9]. It has also been reported that anticoagulation and antiplatelet therapy before catheterization encourage FPA formation [9].…”
Section: Risk Factors Of Fpamentioning
confidence: 99%
“…We identified the following risk factors for complications by literature search: increasing age, female gender, obesity [15], hypertension [16], Peripheral Vascular Disease (PVD), Coronary Artery Disease (CAD) [17], diabetes mellitus [18], renal dysfunction [16] and the intake of antiplatelet and anticoagulant medication [17,19]. In the dataset, we identified these confounding variables through ICD and OPS codes from inpatient and outpatient records of the insurance company.…”
Section: Measurement Of Confoundermentioning
confidence: 99%